2018
DOI: 10.1002/jor.23907
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the expression of matrix extracellular genes and TGFB family members in rotator cuff tears

Abstract: Lack of synthesis of extracellular matrix compounds may contribute to degeneration of the tendons. Thus, we aimed to evaluate the expression of extracellular matrix and TGFB family members in ruptured and non-ruptured tendons of the rotator cuff, as well as the effect of clinical factors on gene expression in tendon samples, and the relationship between histological findings and altered gene expression. Injured and non-injured supraspinatus tendon samples and subscapular non-injured tendon samples were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 45 publications
1
20
0
1
Order By: Relevance
“…Support for the last hypothesis is provided by the finding that the rare alleles of rs3196378 ( COL5A1 ) and of rs1590 ( TGFBR1 ) were only associated with the risk of RCT in males. Both SNPs are located in the 3′‐untranslated region (3′‐UTR), which is involved in the regulation of messenger RNA stability, and the expression of these genes seems to increase in an attempt to repair the degenerated tendon . Moreover, our findings in shoulder tendinopathy are also supported by previous investigations showing the role of the variant of COL5A1 in chronic Achilles tendinopathy as well as soft tissue injuries in rugby athletes .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Support for the last hypothesis is provided by the finding that the rare alleles of rs3196378 ( COL5A1 ) and of rs1590 ( TGFBR1 ) were only associated with the risk of RCT in males. Both SNPs are located in the 3′‐untranslated region (3′‐UTR), which is involved in the regulation of messenger RNA stability, and the expression of these genes seems to increase in an attempt to repair the degenerated tendon . Moreover, our findings in shoulder tendinopathy are also supported by previous investigations showing the role of the variant of COL5A1 in chronic Achilles tendinopathy as well as soft tissue injuries in rugby athletes .…”
Section: Discussionsupporting
confidence: 86%
“…With adjustment for clinical and genetic ancestry covariables, we demonstrated that the rare allele G of TGFB1 rs1800470 contributed to less susceptibility to tears and the G allele of MMP9 rs17576 was involved in the risk of RCT, which was confirmed in the haplotype analysis. An increased expression of TGFB1 and reduced expression of MMPs (such as MMP9 ) in tendons appear to be related to an attempt at new collagen fibers synthesis and assembly . Although evidence of the involvement of these genes in the pathobiology of RCT was already reported, this is the first study to show that SNPs of these genes may modulate the risk of this injury.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In 2018, our group described that the altered expression of the genes COL1A1, COL1A2, COL3A1, COL5A1, FN1, TNC, TGFB1, and TGFBR1 is involved in the process of degeneration in ruptures of the rotator cuff. 34 In a systematic review study, Dabija et al concluded that although previous studies provide preliminary evidence of genetic and family predisposition to RCIs, there is a lack of large genomic studies that can provide more definitive information and guide the early detection of individuals at risk, prophylactic rehabilitation and potential gene therapies and interventions in regenerative medicine. 10 A more recent study conducted an extensive analysis using Gene Expression Omnibus (GEO) gene expression profile gse93661 and bioinformatics analysis to investigate differentially expressed genes (DEGs) in satellite cells between samples of cases of supraspinal injury and subscapular tendon controls.…”
Section: Rotator Cuff Injurymentioning
confidence: 99%